Identifikasi dan Intensitas Rocinela sp. Pada Ikan Kerapu di Pantai Kedonganan, Jimbaran, Bali - Ayu Trisnayanti, Ni Luh; Damriyasa, I Made; Suryaningtyas, Endang Wulandari (Current Trends in Aquatic Science; Vol 2 No 2 (2019), 2019)
This research was aims to determine the intensity level of Rocinela sp. in groupers. Grouper fish samples were taken at Kedonganan Beach, Jimbaran, Bali. Grouper fish is a type of fish that lives around coral reefs, that have a high economic value. Grouper fish sampling was done randomly method, so that the length and weight of the grouper samples used will be more diverse. Fish samples obtained at Kedonganan Beach will be excamine for parasites at the Fisheries Laboratory, Marine and Fisheries Faculty, Udayana University. The grouper samples observed in this study were 40 individuals. The type of parasite found in grouper is Rocinela sp. This parasite belongs to the order of Isopoda which is a type of ectoparasite that attacks fish. Ectoparasites are a type of parasite that infects the outside of a fish's body, such as the gills, mouth, eyes, and operculum. Ectoparasites can cause damage and impaired function in the infected organ. Based on the results of the study found Rocinel sp. in 26 fish sampled with a total number of parasites of 28 individuals. Most of these parasites were found in the gills with a percentage of 92.6% and some were found in the operculum with a percentage of 7.4%. The intensity value of parasitic Rocinela sp. that is 1,067, this value indicates infection of Rocinela sp. which is low in grouper fish at Kedonganan Beach, Jimbaran, Bali.